The Best Strategy For Dealing With Business Conflicts: Strategic Choices In Drafting Clauses In Arbitration Agreements And The Application Of Expedited Procedures - Wiguna, Adhi Gani; Ansari, Teuku Syahrul; Astawa, I Ketut; Setiady, Tri (Gema Wiralodra, 2024)
Arbitration or the root word in (Latin) ''arbitrare'' means "the process or method of deciding a dispute through an independent arbitrator or referee". This definition is one of them because legal experts have different opinions or views even though their opinions have the same meaning. Talking about arbitration or arbitration institutions, there has actually been and has been practiced throughout the centuries for the first time introduced by the Greek community before Christ. As for Indonesia, arbitration is known and recognized by citizens as an alternative to problem solving through non-litigation. Alternative dispute resolution, such as arbitration and mediation, is now a popular choice in resolving business conflicts. The method used to collect data is by conducting literature searches published in scientific research articles and journals. The literature search was conducted using several loaded search engines, such as Google Scholar, Pubmed, and Science Direct.  This method is an alternative that is considered more effective and efficient than going through the courts, because the process is faster, lower costs, and the resulting decisions are final and binding. The purpose of this study is how to choose a strategy in drafting clauses in the Arbitration agreement for dispute resolution